DESKRIPSI KEMAMPUAN BERPIKIR KREATIF ANAK USIA 5-6 TAHUN DALAM KEGIATAN MENGGAMBAR BEBAS DI MASA PANDEMI COVID-19 - Syahra Savira Mokodompit; Setiyo Utoyo; Icam Sutisna (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2021)
The purpose of this study was to determine the description of the creative thinking abilities of children aged 5-6 years in free drawing activities during the COVID- 19 pandemic. The method used in this research is descriptive qualitative. Data collection techniques using were observation techniques, interviews and documentation. The results of the study can be observed based on four indicators on creative thinking, namely (1) thinking fluently, children can smoothly answer teacher questions and smoothly determine the image to be made; (2) flexible thinking, children can think more than one idea so that children can make two kinds of pictures; (3) think original, children can draw independently; and (4) think in detail, the child can give color to the image and can produce clear images.